Adapting Approaches to MECC – for Pre-registration Nursing Education - Michelle Anderson (Welsh Public Health Conference, 2019)
This is an accepted poster presentation for the 2019 Welsh Public Health Conference. It details the adapted approach to delivering Making Every Contact Count (MECC) training, to undergraduate student nurses. The poster highlights where we were, what initial steps were undertaken, adoption of a blended learning approach to delivery. It highlights that students appear to value the changed approach and supports and androgogical approach to student centred learning. Further evaluation is needed to ascertain the feasibility of role-out to other student groups studying nursing